PERANAN SELAT BANGKA SEBAGAI PINTU GERBANG DUNIA MARITIM KOTA PALEMBANG - zusneli zubir (JURNAL PENELITIAN SEJARAH DAN BUDAYA, 2019)
In this paper there are several objectives tobe assessed, first described acondition of a water, in the Bangka Strait which then become the main reference maritime gate of a city, in this case thecity of  that existinthese waters as the main maritime gate way cities described his past through literature references. Second, analyze and synthesize the role of awater, with all the Bangka Strait role as the main door ofthe maritime world by looking at Palembang important role between the time from time to time any authority in the city Palembang. Third, formulate how the waters of the Strait of Bangka controlled and controlled from a region that is in the hinter land city of Palembang so that it looks the main interest will mastery of these waters as the world’s main maritime gate way Palembang becomes central. This paper is astudy of the history of the study of the past, particularly the Bangka Strait as a maritime gateway city of Palembang.As the study of history, the method usedis the historical method, which includes stages in historical method, consists of four stages, namely heuristic, criticism, interpretation and historiography. Based on the study italthough far from the ocean, the city of Palembang in every time and a power that stood there, unable to control the oceans as a maritime powerby empowering the Bangka Straitas the main maritime gate way. The ability to control this can be attributed to the excellent Palembang can utilize the natural conditions that lie Bangka Strait that separates mainland Sumatra island to the mainland island of Bangka very well and right. Bangka Strait referenced and compass every ship that goes from the sea and out to sea. Further more, any ruler in Palembang able to build to build the maritime world in Palembang by making the Bangka Straitas the main gate way to connectinter-city trade, both from China and India in his past, as well as Batavia and Singapore in the next period.The rulers in Palembangwith elegant able to perform the control of politically appropriate and correct over the world which originated from the vast ocean waters of the Strait of Bangka.The control followed by the utilization of natural resources in the region into an economic power but also the power of culture tomake theBangka Strait to become a gate way to the city of Palembang, so the Bangka Strait role as the main gate way to maximum.